2004
DOI: 10.1259/bjr/37893924
|View full text |Cite
|
Sign up to set email alerts
|

Sparing of the penile bulb and proximal penile structures with intensity-modulated radiation therapy for prostate cancer

Abstract: Quality of life is an important consideration in the treatment of early prostate cancer. Laboratory and clinical data suggest that higher radiation doses delivered to the bulb of penis and proximal penile structures correlates with higher rates of post-radiation impotence. The goal of this investigation was to determine if intensity-modulated radiation therapy (IMRT) spares dose to the penile bulb while maintaining coverage of the prostate. 10 consecutive patients with clinically organ confined prostate cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Dosimetric studies of IMRT in the treatment of prostate cancer have shown the ability to reduce radiation dose specifically to proximal penile structures such as the penile bulb. 18,[42][43][44] Radiation dose to the penile bulb has been the subject of several studies concerning radiation-induced ED. 9,10,[30][31][32] Although the results of these reports are often conflicting, there is at least some evidence to suggest that by minimizing radiation dose to the proximal penile structures, the risk of radiation-induced ED may be significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Dosimetric studies of IMRT in the treatment of prostate cancer have shown the ability to reduce radiation dose specifically to proximal penile structures such as the penile bulb. 18,[42][43][44] Radiation dose to the penile bulb has been the subject of several studies concerning radiation-induced ED. 9,10,[30][31][32] Although the results of these reports are often conflicting, there is at least some evidence to suggest that by minimizing radiation dose to the proximal penile structures, the risk of radiation-induced ED may be significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The mean dose to the proximal penile tissues was significantly reduced in IMRT plans with an average of 40%. Kao and colleagues [36] confirmed these results in a trial of ten patients treated by IMRT for PC, reporting a mean dose to the penile bulb of 49 Gy with 3D-CRT compared to 33 Gy with IMRT. Similar results were reported for rectum, while the prostate was adequately covered.…”
Section: Prevention Of Post-radiation Ed and The Value Of Imagingmentioning
confidence: 78%
“…[21][22][23][24] Kao et al compared the dose to the penile bulb using IMRT versus 3D-CRT and found that it was possible to significantly reduce the dose without compromising the dose to the prostate (Table 5). 22 To precisely target the prostate with tighter margins, we currently have 4 fiducial markers implanted in the prostate prior to obtaining planning computed tomography and magnetic resonance imaging. Either 100 mL or 200 mL of saline is instilled in the rectum and the prostate is realigned daily by obtaining pretreatment radiographs and precisely realigning the fiducial markers.…”
Section: Treatment Of Erectile Dysfunctionmentioning
confidence: 99%